2020
DOI: 10.3390/app10207178
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Role of Newly Developed ALBI and mALBI Grades for Treatment of Hepatocellular Carcinoma

Abstract: Hepatocellular carcinoma (HCC) is a leading cause of death worldwide. The selection of therapeutic modalities and the prognosis of affected patients are well known to be dependent not only on the tumor burden but also on the hepatic reserve function. Antiviral treatments for chronic hepatitis related to a viral infection and an increase in cases of nonviral HCC associated with the aging of society have resulted in dramatic changes regarding the characteristics of HCC patients. With recent developments in thera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 81 publications
0
4
0
Order By: Relevance
“…Recently, researchers have reported the usefulness of the ALBI score and ALBI grade, calculated from serum albumin and bilirubin, in assessing hepatic function. 23,38,39 The greatest advantage of ALBI is that it can be obtained easily from routine blood test results. ALBI is worse in patients with hyperbilirubinemia, so as with ICG, it is useful for evaluating hepatic functional reserve in patients with low ICG-R15.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, researchers have reported the usefulness of the ALBI score and ALBI grade, calculated from serum albumin and bilirubin, in assessing hepatic function. 23,38,39 The greatest advantage of ALBI is that it can be obtained easily from routine blood test results. ALBI is worse in patients with hyperbilirubinemia, so as with ICG, it is useful for evaluating hepatic functional reserve in patients with low ICG-R15.…”
Section: Discussionmentioning
confidence: 99%
“…The ALBI score was calculated as − 0.085 × (albumin [g/L]) + 0.66 × log10(− total bilirubin [µmol/L]), and was further categorized into three different grades as the modi ed ALBI grade: grade 1 ( < − 2.60), grade 2a ( > − 2.60 to < − 2.27), grade 2b (≥− 2.27 to ≤− 1.39), and grade 3 ( > − 1.39). 23 The ICG-R15 was the serum ICG level measured 5 minutes after injection of 0.5 mg/kg of ICG. The LHL15 was calculated by [(L15; the radioactivity of the liver at 15 minutes after 99mTc-GSA injection)] / [L15 + (H15; the radioactivity of the heart at 15 minutes after injection)].…”
Section: Preoperative Physical Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Both of these clinical guidelines have incorporated the ALBI scoring system as an important component in their latest version 29 31 . There is growing evidence in clinical practice that the ALBI score/grade is more appropriate than the MELD or CP score 16 , 32 , 33 . Using 2099 data points from HCC patients in a retrospective study, the ALBI grade showed better prognostic performance than that of CP grade in a survival analysis, as well as a better grade distribution 34 .…”
Section: Discussionmentioning
confidence: 99%